Bubbles, booms, and busts the rise and fall of financial assets - Rapp, Donald (Copernicus Books, 2025)
This book provides a thorough explanation of the nature and history of booms, bubbles and busts in financial markets. The first part of the book deals with financial booms and bubbles and how they emerge, develop and collapse. It describes the distribution of wealth, inflation, rationality of bankers, monetary and fiscal policy, the role of central banks, tax policies, social security, US federal, state, municipal and personal debt, and valuation of common stocks. The book describes historical boom/bust cycles including bubbles of the 1720s, the Florida land boom and the stock market in the 1920s, the depression of the 1930s, the S&L scandal of the 1980s, the great bull market of 1982-1995, the crash of 1987, the dot.com mania of 1995-2000, corporate swindles of the 1990s and 2000s, the sub-prime fiasco of the 2000s, and Japan in the late 20th century. Most of the recent wealth generation has derived from increased debt and appreciation of paper assets. The architects of the new economics were Ronald Reagan and Arthur Greenspan. Inevitably, the US Government’s cure for excessive spending and inadequate revenues is to increase spending and cut revenues. American voters must choose between “tax and spend” Democrats and “spend and borrow” Republicans. The theme of American finance was uttered by VP Cheney: “Deficits don’t matter”. Manias, bubbles, crashes: introduction - The human element - The rise of manias and bubbles - Fueling the boom - Wealth - inflation - Speculations, bootstraps, swindles - The rationality of investors - The rationality of bankers and experts?- monetary policy and the federal reserve system - Fiscal policy, taxes - Inequality - Debt - Deposit insurance - Regulation, deregulation and no regulation - Pension plans - The valuation of common stocks - Internal feedback - edogenous risk - When the bubble pops - The united states: introduction - Florida land boom 1920s - The roaring 20s stock market - The great depression of of the 1930s - Savings and loan scandal of the 1980s - The bull market of 1982-1995 - The crash of 1987 - The dot.com mania - Other bubbles and swindles of the late 1990s and 2000s - The sub-prime real estate boom 2001-2007 - Japan 1970-2007: overview - Stock market.-. real estate - Collape of the bubble - East asia - Domino effect - Other notable bubbles and busts: the tulop craze 1634-7 - South seas bubble - John law's mississippi company. albania 1990s.